2020
DOI: 10.1177/1055665620982789
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Growth of the Palatal Plates in the Cleft Lip and Palate

Abstract: Objective: This is a prospective study examining palatal casts from patients with unilateral cleft lip and palate (UCLP) in the first month of life, immediately before cheiloplasty, and immediately before palatoplasty. None of the patients receives presurgical orthopedics (nasoalveolar molding). Design: In this prospective study, upper arch plaster models were taken 3 times during the treatment: in the first month of life (T1), before the cheiloplasty (T2), and before the palatoplasty (T3). Anatomic landmarks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…In agreement with our results, a previous study demonstrated that UCL/P babies had a significant spontaneous palatal narrow with no intervention performed 35 . Although this study did not measure the cleft gap and arch width in nontreated babies, such as Pontes et al, 35 our results demonstrate that the orthopedic apparatus allowed the normal maxillary growth of the palate of the cleft babies with the increase in the AP and length.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with our results, a previous study demonstrated that UCL/P babies had a significant spontaneous palatal narrow with no intervention performed 35 . Although this study did not measure the cleft gap and arch width in nontreated babies, such as Pontes et al, 35 our results demonstrate that the orthopedic apparatus allowed the normal maxillary growth of the palate of the cleft babies with the increase in the AP and length.…”
Section: Discussionsupporting
confidence: 92%
“…A 1,74 mm (17,83%) of reduction was found before cheiloplasty, this is associed to a natural growth, suggesting that the palatal plates may have narrowed spontaneously. 4 A 7.81 mm (79.82%) reduction was found after cheiloplasty. Our data corroborate the study by Huang et al 23 and Pontes et al 4 Despite the fact that, when treatment started, patients in G2 (FMO) showed wider clefts with a smaller circumferenceaccording to Peltomäki et al, 24 in patients with wider clefts, smaller arch circumferences, shorter arch lengths, or both, growth was hinderedin the group that was treated with FMO an appropriate cleft closure was achieved before surgery (closure amounted to 52.07%, 5.92 mm between T1 and T3).…”
Section: Discussionmentioning
confidence: 86%
“…[1][2][3] Nevertheless, it has been reported that the use of PSIO is not always necessary for a proper alveolar growth, and previous studies suggest that the cleft size may be reduced without orthopedic devices. 4,5 Many studies have published case series of patients who were treated either with or without pre-surgical orthopedics, but few of them compare case series of patients with and without such treatment.…”
Section: Introductionmentioning
confidence: 99%
“…8,16,17,19 Cheiloplasty can limit anterior palate development, but not in the posterior region, because of the continuous pressure exerted by the healing tissue on the dental arch. 5,8,16,20 The unilateral growth of the dental arch suggests that both cleft width and treatment protocol influenced palate formation.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] Anatomic landmarks and linear parameters were used in the dental arch evaluations according to previous studies with children. 8,9,16,19,20 The following parameters were measured: P-P' -Anterior cleft width (straight line between the most anterior points of the alveolar bone crests); M-M' -Middle cleft width (straight line between the points located in the medial region of the palatal segments adjacent to the cleft); U-U' -Posterior cleft width (straight line between the most posterior points of the palatal segments adjacent to the cleft); I-C' -Anterior intersegment distance (between the interincisive point and the primary canine cusp in the smaller bone segment); I-C -Anterior intrasegment distance (between the interincisive point and the primary canine cusp in the greater bone segment); I-T' -Total intersegment distance (between the interincisive point and the tuberosity of the smaller bone segment); I-T -Total intrasegment distance (between the interincisive point and the tuberosity of the greater bone segment); C'-T' -Cleft-side canine tuberosity distance (between the primary canine cusp and the tuberosity of the smaller bone segment); and C-T -Non-cleft-side canine tuberosity distance (between the primary canine cusp and the tuberosity of the greater bone segment). All the parameters were quantified in mm (Figure 1).…”
Section: Digital Anthropometric Analysismentioning
confidence: 99%